Analisis Potensi Likuifaksi dan Perencanaan Perbaikan Tanah pada Bangunan Pemecah Gelombang di Wilayah Pantai Bali Selatan - Muntaha, Moh.; Ralindra, Deris Faisa; Maharani, Nadia Zhafirah; Mawardi, Amalia Firdaus; SUngkono, Sungkono; Sumirman, Edy; Rahardjo, Ibnu Pudji; Affandhie, R Buyung Anugraha; Prayitno, Achmad Faiz Hadi (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
Liquefaction is the condition of the soil that loses shear strength due to an earthquake, so the capacity of the soil decreases suddenly. Liquefaction occurs in water-saturated sand soils, such as in breakwater of South Bali coast with the magnitude earthquake of 6.8 based on BMKG data in 2011. This condition allows liquefaction to occur under the breakwater. This study aims to identify the potential and thickness of the liquefaction layer based on the N-SPT value at 4 bore hole using 3 methods, namely the Seed-Idriss method, the NCEER method, and the Tokimatsu-Yoshimi method, and design ground improvement with vibro compaction to overcome liquefaction problems. Based on the results of 3 methods analysis, the potential for liquefaction occurred in all bore hole zones with a thickness of 5 to 9 m from the ground surface. The ground improvement design uses vibro compaction with a triangular pattern, spacing 2.1 m. Ground improvement increases the liquefaction FS value, so the potential for liquefaction in all bore hole zones does not occur